Synthesis of new 1,3,4-oxadiazole and benzothiazolylthioether derivatives of 4-arylmethylidene-3-substituted-isoxazol-5(4H)-one as potential antimycobacterial agents - Chavan, Abhijit P.; Deshpande, Rujuta R.; Borade, Nandkumar A.; Shinde, Abhijit; Mhaske, Pravin C.; Sarkar, Dhiman; Bobade, Vivek D. (Medicinal Chemistry Research, 2019)
A new series of 4-[(substituted benzylidene)-3-[(5-(pyridine-4-yl)-1,3,4-oxadiazole-2-ylthio)-methyl]i soxazol-5(4H)-one (6a-g) and 4-(substituted benzylidene)-3-((benzo[d]thiazol-2-ylthio)methyl)isoxazol-5(4H)-one (8a-g) was synthesized. All the synthesized compounds were screened for antitubercular activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) and antibacterial activity against Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), Bacillus subtilis (NCIM 2162). Amongst the synthesized 1,3,4-oxadiazole and benzothiazoyl thioether derivatives, compounds 6b and 8b showed excellent antimycobacterial activity and compounds 6b, 8a, 8b, and 8d showed excellent antibacterial activity against all tested antibacterial strains. The synthesized compounds were further evaluated for their cytotoxic activity against the HCT 116 and HeLa cancer cell lines. The 1,3,4-oxadiazole and benzothiazoyl thioether derivatives 6a-g and 8a-g did not show cytotoxicity.
Keywords: 1; 3; 4-Oxadiazole; antibacterial activity; Antitubercular activity; Benzothiazol; Isoxazol-5(4H)-one; Thioeteher

Synthesis and antimycobacterial screening of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline derivatives - Thakare, Prashant P.; Walunj, Yogesh; Chavan, Abhijit; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Journal of Heterocyclic Chemistry, 2020)
A new series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline (6a-t) have been synthesized by a click reaction of 4-(4-ethynyl-1-phenyl-1H-pyrazol-3-yl)quinoline (4a-d) with a substituted benzyl azide (5a-e). The starting alkyne derivatives4a-dare obtained from Bestmann-Ohira reaction of 1-phenyl-3-(quinolin-4-yl)-1H-pyrazole-4-carbaldehyde and dimethyl(1-diazo-2-oxopropyl)phosphonate. The newly synthesized compounds are screened againstM. tuberculosisH37Ra dormant and active,Escherichia coli,Pseudomonas fluorescence,Staphylococcus aureusandBacillus subtilisstrains at 30 mu g/mL concentration. Most of the screened compounds showed good to moderate antibacterial activity againstS. aureus,B. subtilis, andMycobacterium tuberculosisH37Ra strains. The synthesized derivatives of quinolinyl-pyrazole-4-carbaldehyde and quinolinyl-pyrazole-4-ethyne reportd good to moderate activity against both strains ofM. tuberculosisH37Ra. Ten derivatives of quinolinyl-pyrazole presented good activity againstB. subtilis. These results suggested that further optimization and development of quinolinyl-pyrazolyl-1,2,3-triazole moeity could serve as lead compounds for antimycobacterial activity.

Synthesis and antimycobacterial screening of a novel series of alpha-amino acids containing thiazole linker - Nalawade, Jitendra L.; Mhaske, Pravin C.; Shinde, Abhijit D.; Chavan, Abhijit P.; Abhale, Yogita K.; Sarkar, Dhiman; Bobade, Vivek D. (ARKIVOC, 2022)
A small focused library of uncommon (S)-2-amino-3-(4-(((4-methyl-2-arylthiazol-5-yl)methyl)amino)phenyl) propanoic acid (5a-e) and (S)-2-amino-3-(4-(((2-arylthiazol-4-yl)methyl)amino)phenyl)propanoic acid (9a-d) derivatives have been efficiently synthesized by employing molecular simplification. The title compounds were screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis (BCG) strains. The cytotoxicity study was conducted against primary Human Umbilical Vein Endothelial Cells (HUVECs), on two different human tumor cells HeLa, and HCT 116 and was observed non-toxic to host cells.
Keywords: Amino acid; antibacterial activity; Cytotoxicity; Mycobacterium tuberculosis; synthesis; Thiazole

Synthesis of new thiazole and pyrazole clubbed 1,2,3-triazol derivatives as potential antimycobacterial and antibacterial agents - Jagadale, Shivaji M.; Abhale, Yogita K.; Pawar, Hari R.; Shinde, Abhijit; Bobade, Vivek D.; Chavan, Abhijit P.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compounds, 2022)
New series of 4-methyl-2-(4-substituted phenyl)-5-(4-((4-(4-substituted phenyl)-1H-1,2,3-triazol-1-yl)methyl)-1-phenyl-1H-pyrazol-3-yl)thiazole, 6a-t and 4-(1,3-diphenyl-1H-pyrazol-4-yl)-1-((1,3-diphenyl-1H-pyrazol-4-yl)methyl )-1H-1,2,3-triazole, 11a-o derivatives have been synthesized by applying copper-catalyzed [3 + 2] cycloaddition reaction. The newly synthesized 1,3-thiazolyl-pyrazolyl-1,2,3-triazole (6a-t) and bis-pyrazolyl-1,2,3-triazole (11a-o) derivatives were screened for in vitro antimycobacterial activity against M. Tuberculosis H37Ra dormant and active and antibacterial activity against four pathogenic bacteria, E. coli (NCIM 2576), P. flurescence (NCIM 2059), S. aureus (NCIM 2602) and B. subtilis (NCIM 2162). Compounds 6a, 6f, 6j, 11e and 11m showed good activity against M tuberculosis H37Ra Active strain, also compounds 6g, 6h, 11f, 11n and 11o showed good activity against M tuberculosis H37Ra Dormant strain. Compounds 6b, 6i, 6l, 6o, 6r, 11k, 11l and 11m showed good activity against B. subtilis with IC50 1.99-2.96 mu g/mL. The antibacterial activity of thiazolyl-pyrazolyl-1,2,3-triazole and bis-pyrazolyl-1,2,3-triazole derivatives suggested that, these derivatives could lead to new compounds for treatment against bacterial infection.
Keywords: 123-Triazole; antibacterial activity; antimycobacterial activity; Pyrazole; Thiazole

Synthesis and antimicrobial evaluation of novel 2'-aryl-4-aryl-2,4'-Bisthiazole and 2'-aryl-4-Pyridyl-2,4'-bisthiazole derivatives as potential antibacterial agents - Nalawade, Jitendra; Shinde, Abhijit; Abhale, Yogita K.; Nandurkar, Yogesh; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compound, 2024)
In continuation of our research work to explore bisthiazole derivatives as potential antimicrobial agents, herein we reported the synthesis of a series of novel 2'-aryl-4-aryl-2,4'-bisthiazole (7a-t) and 2'-aryl-4-pyridyl-2,4'-bisthiazole (9a-l) by cyclocondensation of 2-aryl thiazole-4-carbothioamide 5a-d with 2-bromo-1-arylethanone (6a-e) and bromo-1-(pyridin-2/3/4-yl)ethanone (8a-c), respectively. These novel candidates were evaluated in vitro for their antibacterial potential against four pathogenic bacteria, Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), and Bacillus subtilis (NCIM 2162). The synthesized compounds were also screened for their in vitro antifungal activity against Candida albicans (NCIM 3100). Among them, compounds 7b, 9d, 9 g, 9i, and 9 l exhibited excellent antibacterial activity with MIC 2.1 to 12.3 mu g/mL against all tested strains. Most of the compounds reported moderate antifungal activity. The pyridine ring-substituted bisthiazole reported good to excellent antibacterial activity as compared to phenyl ring-substituted bisthiazole. The potential antibacterial activity suggested that bisthiazole derivatives could assist in the development of lead compounds to treat microbial infections.
Keywords: 24'-bisthiazole; antibacterial activity; Antifungal activity; cyclocondensation